KNOWLEDGE, ATTITUDE AND PERCEPTION OF ANAESTHESIA AND PRACTICE OF ANAESTHESIA DURING NON-EMERGENCY SURGERY- A CROSS-SECTIONAL STUDY - Dr. R Ramasamy MD; Dr. Sivaranjani KS MDS; Dr. Parthibhan S; Dr. Gunaseelan.C (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Enhancing Patient Awareness and Addressing Apprehensions in Anaesthesia:Anaesthesia plays a pivotal role in modern healthcare, ensuring patient safety and comfort during surgical procedures. It achieves this by effectively managing pain and altering levels of consciousness¹. However, a significant issue within the field is the inadequate knowledge among the general population regarding anaesthesia, which often leads to unwarranted fears and misconceptions about its rare risks and complications².One contributing factor to this knowledge deficit is the minimal interaction anaesthesiologists typically have with conscious patients compared to other healthcare professionals³. This limited contact can exacerbate patient apprehensions, resulting in severe anxiety before surgery. Anxiety can trigger activation of the sympathetic nervous system, potentially causing elevated blood pressure, tachycardia, and arrhythmias, which may negatively affect surgical outcomes⁴.The process of informed consent is crucial for addressing these challenges. Effective informed consent involves active communication between the healthcare provider and the patient. It ensures the treating physician explains the nature and purpose of the proposed procedure, along with the potential risks and benefits, fostering trust and alleviating anxiety⁵.